Automated content sizing using accelerometer - Ng, Yun Hao (2014)
The purpose of this research is to study the technology of mobile accelerometer in mobile zooming feature. Accelerometer is a kind of device that built in mobile device in order to detect motion. Type of accelerometer that built in mobile device is triaxial accelerometer which detects motion based on three different axes, X-axis, Y-axis and Z-axis. In this research, algorithm is developed to track the value changed in Z-axis when user moved the mobile device. The content on the screen of mobile device zoomed in when Z-axis increase, vice versa the content on the screen of mobile device zoomed out when Z-axis decrease. Similar existing systems are studied and compared in order to study the similarity and feasibility of the research. Methodology is deployed and the whole research followed the methodology which starts from planning, analysis, design, implementation, testing and lastly results inspection. In design and implementation, the value of Z-axis is tracked and used in the zooming algorithm. The algorithm is designed to zoom in the photo when the value of Z-axis increase and vice versa. The results are shown and the objectives of this research are met. Advantages, disadvantages and constraints of this research are discussed and explained further in this document. Future work are also explained in detail in order to improve the results of this research. In conclusion, the objectives of this research are met although there are few drawbacks during the development.